Penggunaan Saluran Komunikasi (Internet) Dalam Penyediaan Informasi Pertanian Di Bpp Sepaku Kecamatan Sepaku Kabupaten Penajam Paser Utara: The Use of Communication Channels (Internet) In Provision of Agricultural Information At BPP Sepaku, Sepaku District, Penajam Paser Utara Regency - Tiara Pebrianti; Syarifah Maryam; Eko Harri Yulianto (Agrifarm : Jurnal Ilmu Pertanian, 2023)
In the era of increasingly strong globalization, mastery of Information and Communication Technology is a necessity that is no longer negotiable. Technology also plays an important role in the development of agriculture. One example of Information and Communication Technology is the internet. The Internet presents the world without boundaries. Through this facility, it is hoped that it can be used to find all the information needed and can also be used by rural communities to improve economic welfare. The purpose of this study was to determine the level of use of communication channels (internet) by agricultural extension workers, to find out how to provide agricultural information and the relationship between the use of communication channels (internet) and the provision of agricultural information by extension workers at BPP Sepaku, Sepaku District. The sampling method used a saturated sample or census with 11 respondents. The data collected in this study are primary data and secondary data. The method of data collection was carried out by observation and direct interviews with respondents. Data analysis used descriptive qualitative method. The results showed that the extension workers in the use of communication channels (internet) were in the high category and the provision of agricultural information in the very useful category. The relationship between the use of communication channels (internet) and the provision of agricultural information shows a high or strong relationship with a Pearson Correlation (r) value of 0,669 Keywords: Internet Media, Agricultural Information, Extension.